RECYCLE PERFORMER DISTRIBUTION STUDY OF MINERAL WATER PLASTIC BOTTLE WASTE (CASE STUDY: BANDUNG CITY) - Hapsari, Hermala Nindya; Damanhuri, Tri Padmi (Jurnal Teknik Lingkungan, 2009)
Abstract: Mineral water plastic bottle have become one of drinking water alternative for society at metropolises such as Bandung City. Consumption of mineral water plastic bottle by society will evoke high plastic waste generation. Mineral water plastic bottle was utilize from Polyethylene Terephtalate's (PET) material and Polypropylene (PP) material. Both of plastic material is a constitutes plastic type that can be recycle. Recycle constitutes is one of the effective ways in waste management for reduce the mineral water plastic bottle waste generation at final disposal (TPA). Mineral water plastic bottle composition at TPA Sarimukti on year 2008 is 1.35% of total amount wastes generates in Bandung City. Plastic waste reduction at TPA takes down from informal sector role that consisting of, pemulung, tukang loak, lapak and bandar. Survey's result that is done at Bandung's City exists 365 recycle performer that consisting of 130 pemulung, 130 tukang loak, 44 numbers lapak, 33 bandar kecil and 28 bandar besar outgrow. According at classification bases on PD. Kebersihan service area therefore at North Bandung exists 17 recycle performer, in East Bandung exists 25 recycle performer, South Bandung exists 20 recycle performer, and West Bandung exists 43 recycle performer. Most of recycle performer exist in Western Bandung because at West Bandung's region there is a lot of available textile mills and also plant wide toy which need raw materials from recycle plastics.Key words: Mineral Water Plastic Bottle, Polyethylene Terephtalate (PET), Recycle Performer, Bandung city Abstrak: Air minum dalam kemasan saat ini sudah menjadi salah satu alternatif air minum bagi masyarakat di kota-kota besar salah satunya Kota Bandung. Konsumsi air minum dalam kemasan oleh masyarakat akan menimbulkan timbulan sampah plastik yang jumlahnya cukup tinggi. Air minum dalam kemasan dibuat menggunakan bahan Polyethylene Terephtalate (PET) dan Polypropylene (PP). Kedua bahan ini merupakan jenis-jenis plastik yang dapat di daur ulang. Daur ulang merupakan salah satu cara pengelolaan sampah yang efektif untuk mereduksi timbulan sampah plastik air minum dalam kemasan di TPA. Komposisi air minum dalam kemasan di TPA Sarimukti pada tahun 2008 adalah sebesar 1.35% dari total sampah yang ada. Reduksi sampah plastik air minum dalam kemasan di TPA tidak lepas dari peranan para pelaku daur ulang sektor informal yang terdiri dari, pemulung, tukang loak, lapak serta bandar.Dari hasil survey yang dilakukan di Kota Bandung terdapat 365 pelaku daur ulang yang terdiri dari 130 orang pemulung, 130 orang tukang loak, 44 buah lapak, 33 buah bandar kecil dan 28 buah bandar besar. Apabila di klasifikasi berdasarkan daerah pelayanan PD. Kebersihan maka di Bandung Utara terdapat 17 pelaku daur ulang, Bandung Timur terdapat 25 pelaku daur ulang, Bandung Selatan terdapat 20 pelaku daur ulang, dan Bandung Barat terdapat 43 pelaku daur ulang.Bandung Barat memiliki jumlah pelaku daur ulang yang paling banyak di karenakan di daerah Bandung Barat banyak terdapat pabrik-pabrik tekstil maupun pabrik mainan yang membutuhkan bahan baku dari plastik daur ulang. Kata kunci: Air Minum Dalam Kemasan, Polyethylene Terephtalate (PET), pelaku daur ulang, Kota Bandung